Urgensi Arsip Dalam Pembuktian Dan Perlindungan Hak-Hak Keperdataan Di Negeri Rumahkay Kecamatan Amalatu Kabupaten Seram Bagian Barat - Syadzwina Hindun Nabila (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Increasing public awareness of the importance of civil law to uphold rights and justice in everyday life, especially in terms of ownership, agreements, and other matters between individuals or legal entities. However, civil law must be balanced with the awareness of the importance of archives to verify and protect civil rights.Purposes of Devotion: To provide understanding and knowledge to the public especially in providing urgent knowledge of archives in proof and protection of privacy rights. Method of Devotion: The dedication method used is the method of advocacy and support of the State House Society, especially in providing urgent knowledge of archives in the proof and protection of privacy rights.Results of the Devotion: Essential evidence in the proof of civil matters include written or written evidence; witnesses; assumptions; confessions; and oaths from sources or expert statements. In the process of settling a case in court, written or written evidence is more important than any other evidence. The judge uses the legal means of proof to seek formal truth to seek material truth. Because this means of proof is also meant to assist in proof in disputes and provide legal protection.